Implementation of Student Worksheets Based on Genre Pedagogical Model for Descriptive Text Writing Ability Profile in Elementary School - Agusti Liani , Gita (ATTA`DIB, 2025)
The purpose of this study is to develop student worksheet assisted by the Canva application with a genre pedagogical model and a profile of descriptive text writing abilities for fifth-grade elementary school students. The type of research used is Research and Development (R & D) research using the ADDIE model. Based on the results of expert validation, it shows a very valid level of 0.94-1.00 and the expert agreement criteria get a percentage of 67% - 100% with a high and almost perfect category. Based on the results of the study after the implementation of student worksheet based on the genre pedagogical model assisted by the Canva application and the profile of descriptive text wrote abilities is the result of data analysis of descriptive text writing abilities that include three aspects, namely topics, section descriptions, and conclusions. In the topic aspect there are 7 students with very good categories, and 13 students with good categories. For the section description aspect there are 9 students in the very good category, 11 students with good categories. Finally, the conclusion aspect has 1 person with a very good category, 15 students with good categories and 4 students with sufficient categories. The use of student worksheets based on the genre pedagogical model assisted by the Canva application obtained the highest results in the topic and section description aspects and still found sufficient categories in the conclusion aspect, this will be the focus for providing more practice in wrote descriptive texts.